A Network Proposal for the Caput Adriae in the Middle and Recent Bronze Ages (MBA2 - RBA1) - Giulio Simeoni (IpoTESI di Preistoria)
Caput Adriae, the territory between Istria and Friuli, experienced a systematic occupation both through the spread of fortified settlements in Istria, Karst and Upper Friuli, and through the emergence of numerous open settlements in the lowlands, between the final phases of the Early Bronze Age and the Late Bronze Age. In the present work, through the application of Network Analysis on a ceramic sample, a proposal is made of the system of relations created, during this period, between the Caput Adriae contexts.